A Cell-Phone-Based Acoustofluidic Platform for Quantitative Point-of-Care Testing - Liying Zhang, (ACS Nano, 2020)
Acoustofluidic methods, with advantages including simplicity of device design, biocompatible manipulation, and low power consumption, have been touted as promising tools for point-of-care (POC) testing. Here, we report a cellphone-based acoustofluidic platform that uses acoustic radiation forces to enrich nanoscale analytes and red and green fluorescence nanoparticles (SiO(2)@R and G@SiO(2)) as probes for POC visual testing. Thus, the color signals from the fluorescent probes are enhanced, and colorimetric sensitivity is significantly improved. As a POC demonstration, the acoustofluidic platform is used to detect hemoglobin (Hb) from human blood, resulting in a rapid and straightforward measurement of normal blood Hb levels. Combining an acoustofluidic-based nanoparticle-concentration platform with cell-phone-based colorimetry, our method introduces a potential pathway toward practical POC testing.